Developing Critical Thinking Skills Through Reading And Writing - Abdullaeva Umida Nigmatullayevna; Alimardonova Marjona Olimjon qizi (Euro Asian Journal Publishing, 2024)
Creating basic considering aptitudes and basic considering mien in college understudies has been set as a essential objective in higher instruction for decades. As of late it has ended up more critical in actualizing this objective to upgrade students' employability within the fast-changing working environment. This ponder explored the viability of creating basic thinking through literature perusing. A number of procedures are consolidated into the course plan: perusing comprehension pop tests, learning log, bunch introductions, guided in-class dialog with Socratic addressing abilities and person essay-question reports
Keywords: fast-changing; pop tests; learning log